A comparison between major chemical markers of the cultivated and wild harvested Siphonochilus aethiopicus, African ginger, from Mpumalanga, South Africa, using Liquid Chromatography-Mass Spectrometry - Tina Chunga; Sechaba Bareetseng; Jeremiah Senabe; Ebrahim Wadiwala (Open Journal of Pain Medicine - Peertechz Publications, 2022)
Siphonochillus aethiopicus, known as African ginger, is indigenous to South Africa and has multiple traditional uses in health to treat human diseases. The multiple traditional uses of African ginger have exacerbated the over-harvesting of the plant species from the wild for trade on the traditional medicine market. The wild populations of African ginger have almost completely depleted from the wild and a few African ginger cultivation sites have been established in South Africa, to conserve the plant species.  The aim of the study was to compare the major chemical markers of the cultivated and wild harvested African ginger from Mpumalanga using Liquid Chromatography-Mass Spectrometry (LC-MS). The Council for Scientific and Industrial Research (CSIR) wild-harvested African ginger dated 2010 was used as a reference sample for comparison purposes. The LC-MS data generated from the ethanol extracts of the cultivated African ginger detected the presence of 4,4a,5,8a,9-tetrahydro-3,5,8a-trimethylnaptho[2,3-b]furan-8. This chemical marker was also detected in the wild harvested African ginger as compared to a previous study, which auto oxidised in the referenced sample over time. This study supports the efforts to conserve African ginger through cultivation for further development in commercialisation.